Design Of E-Wallet And Loyalty Application Using Aes Model On Coffee Terminal - Hafiza Siraj Abshar; Heri Wahyudi; Asep Sudrajat; Muhammad Syukri (Majalah Bisnis & IPTEK, 2025)
This research seeks to tackle the issues of transaction efficiency, payment convenience, transaction security, and minimal consumer involvement encountered by "Terminal Coffee" Coffee Shop. These concerns stem from the sluggish traditional payment system, the lack of ease in transactions, and the need for enhanced transaction security. Furthermore, insufficient client interaction is a significant issue. This research employs application development utilizing Android Studio, JavaScript, Java, and Kotlin. This application seeks to enhance transaction efficiency by facilitating quicker and more convenient payments for Terminal Coffee patrons. The app will use enhanced transaction security mechanisms to safeguard client data and mitigate fraud. The research will focus on enhancing customer engagement through the development of an interactive and compelling loyalty program. The app will enable customers to engage with the coffee shop in a more personalized way, enhancing their overall experience through technology. The research will deliver a comprehensive financial management system that facilitates clients in overseeing their finances about purchases and expenditures at Terminal Coffee. This program will enhance spending visibility, facilitate financial planning, and optimize client financial management efficiency. This research is anticipated to significantly enhance Terminal Coffee's transaction efficiency, security, consumer engagement, and financial management. Moreover, the built application enhances customer experience and facilitates the growth of Terminal Coffee's business.